Purifikasi Parsial Enzim Ekstraseluler (Anoxybacillus sp.) yang Diisolasi dari Sumber Air Panas Bukit Kili Solok serta Aplikasinya untuk Menghidrolisis Limbah Berserat - Octarya, Zona; Syukur, Sumaryati; Purwati, Endang (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
Termostable enzyme from thermophilic bacteria is very potential to improve technical enzyme in industry which used hightemperature. High water temperature exerts selection pressure on microbial species leading to specific flora that survivesand tolerates heat stress. The relative isolation and unique physical properties of Bukit Kili Ketek Hot Springs in Solok,West Sumatera may yield unique thermophiles. The generation of extracellular enzymatic bacterial is highly desirable forproduction of hydrolitic enzymes, which are useful in various industrial application and in animal feeds. This study,conducted to purify extracellular enzymes from thermophilic bacteria (Anoxybacillus sp.). This bacteria was isolated inBukit Kili Ketek Hot Springs, and after identified by analysis of 16S rRNA gene, 97% of similiarty with Anoxybacillus sp.was of obtained. The temperature of the hot waters was 52°C and the pH was 8. Extracellular and hydrolytic enzymeproduction were screened by qualitative SDS-PAGE method. SDS-PAGE analysis gave protein bands at ±110 kDa, ±80 kDa,±60 kDa, 50 kDa, 25 kDa, and ±10 kDa, respectively. Extracellular enzymes were used to degrade cellulose waste. Thecellulose activity for degradation of baggasse and pineapple pulp was 0,451 IU/mL and 0,310 IU/mL at 50°C and pH 6.